Assessing the efficacy and ecology of biocontrol and biomanipulation for managing invasive pest fish. Issue 5 (22nd July 2015) - Davies, Gareth D.; Britton, J. Robert
Summary: Management of non‐native species aims to prevent biological invasions using actions including control and containment of the potential invader. Biocontrol and biomanipulation strategies are used frequently to reduce population sizes of non‐native species and reduce their ecological impacts and dispersal rates. Assessments of the efficacy of biocontrol and biomanipulation actions for managing non‐native pest fish, and the ecological mechanisms involved, were studied here using lentic populations of the invasive fish Pseudorasbora parva . Biocontrol was through release of the indigenous piscivorous fish Perca fluviatilis and biomanipulation through intensive fish removals. A combined biocontrol and removal programme was completed in an invaded pond over two reproductive seasons. Almost 10 000 P. parva were removed, with cumulative removal numbers significantly related to their decreased abundance (>60 to <0·1 m −2 ). Ten adult P .  fluviatilis were also released initially and reproduced each season. Analyses revealed P. parva contribution to P .  fluviatilis diet was high initially, but decreased as P. parva abundance reduced. Individual contributions of the management actions to declined P. parva abundance were difficult to isolate. The individual effects of biocontrol and removals on P. parva populations were then tested using a field trial in replicated pond mesocosms over three reproductive seasons. Replicates started with 1500 P. parva . The control (no interventions) revealed no significant temporal changes in P. parva abundances. In the removal treatment, where over 17 000 P. parva were removed per replicate over the trial, abundance declined initially, but increased significantly after each reproductive season as remaining fish compensated through increased reproductive output. In the biocontrol, abundance declined and remained low; analyses revealed P. parva were an important dietary component of larger P. fluviatilis, with predation suppressing compensatory responses. Synthesis and applications . Biocontrol and removals can significantly reduce abundances of lentic populations of small invasive fishes. Removals provide short‐term population suppression, but high effort is needed to overcome compensatory responses. Biocontrol can provide longer‐term suppression but could invoke unintended ecological consequences via 'stocking‐up' food webs. Application of these results to decision‐making frameworks should enable managers to make more objective decisions on risk‐commensurate methodologies for controlling small invasive fishes. Abstract : Biocontrol and removals can significantly reduce abundances of lentic populations of small invasive fishes. Removals provide short‐term population suppression, but high effort is needed to overcome compensatory responses. Biocontrol can provide longer‐term suppression but could invoke unintended ecological consequences via 'stocking‐up' food webs. Application of these results to decision‐making frameworks should enable managers to make more objective decisions on risk‐commensurate methodologies for controlling small invasive fishes.